Opportunity Recognition Amongst Entrepreneurs - Agarwal, Vikas (2009)
This research paper focuses mainly on various underlying issues of opportunity recognition that are faced by entrepreneurs. I have tried to understand the factors that help people to discover and execute business opportunities.